Molecular Poltergeists: Mitochondrial DNA Copies (numts) in Sequenced Nuclear Genomes - Hazkani-Covo, Einat (Public Library of Science, 2010)
The natural transfer of DNA from mitochondria to the nucleus generates nuclear copies of mitochondrial DNA (numts) and is an ongoing evolutionary process, as genome sequences attest. In humans, five different numts cause genetic disease and a dozen human loci are polymorphic for the presence of numts, underscoring the rapid rate at which mitochondrial sequences reach the nucleus over evolutionary time. In the laboratory and in nature, numts enter the nuclear DNA via non-homolgous end joining (NHEJ) at double-strand breaks (DSBs). The frequency of numt insertions among 85 sequenced eukaryotic genomes reveal that numt content is strongly correlated with genome size, suggesting that the numt insertion rate might be limited by DSB frequency. Polymorphic numts in humans link maternally inherited mitochondrial genotypes to nuclear DNA haplotypes during the past, offering new opportunities to associate nuclear markers with mitochondrial markers back in time.